2003
DOI: 10.4049/jimmunol.170.10.5045
|View full text |Cite|
|
Sign up to set email alerts
|

Mast Cells Express Novel Functional IL-15 Receptor α Isoforms

Abstract: Mast cells previously have been reported to be regulated by IL-15 and to express a distinct IL-15R, termed IL-15RX. To further examine IL-15 binding and signaling in mast cells, we have studied the nature of the IL-15R and some of its biological activities in these cells. In this study, we report the existence of three novel isoforms of the IL-15Rα chain in murine bone marrow-derived mast cells as a result of an alternative exon-splicing mechanism within the IL-15Rα gene. These correspond to new mRNA transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 49 publications
3
37
0
Order By: Relevance
“…All primers were purchased from Metabion. cDNA was amplified by standard PCR procedure as described previously (30). To evaluate mRNA expression semiquantitatively, in addition to the PCR product from 35 cycles, 15 l of the PCR product from the 25 cycles and the 30 cycles were run simultaneously.…”
Section: Rt-pcrmentioning
confidence: 99%
“…All primers were purchased from Metabion. cDNA was amplified by standard PCR procedure as described previously (30). To evaluate mRNA expression semiquantitatively, in addition to the PCR product from 35 cycles, 15 l of the PCR product from the 25 cycles and the 30 cycles were run simultaneously.…”
Section: Rt-pcrmentioning
confidence: 99%
“…Tagaya and co-workers [32] report that signalling during IL-15-induced mast cell proliferation is associated with phosphorylation of STAT-5 and not STAT-6, while Masuda and co-workers [34] report that signalling during IL-15-induced IL-4 expression in mast cells is associated with phosphorylation of STAT-6 and not STAT-5. Finally, Bulanova and co-workers [39] report that IL-15 induced phosphorylation of both STAT-5 and STAT-6. This implies either that IL-15 can signal using a single receptor via either STAT-5 or STAT-6, or two distinct receptor systems and signalling pathways are involved.…”
Section: Discussionmentioning
confidence: 99%
“…This implies either that IL-15 can signal using a single receptor via either STAT-5 or STAT-6, or two distinct receptor systems and signalling pathways are involved. Recently, Bulanova and co-workers [39] demonstrated that mBMMC express alternatively spliced transcripts for the IL-15Ra. We did not detect these transcripts in our mBMMC, however the full length transcript for the IL-15Ra and the IL-15Ra transcript variant 2D were present (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The NLS of IFN-␥ is involved in complexing STAT1␣ with nuclear importin ␣ for nuclear translocation of STAT1␣, and is crucial for the biological properties of IFN-␥ (73). It is known that STAT3/5/6 are involved in IL-15 signaling in mammals (74) and thus the NLS in trout IL-15 might function to assist the translocation of the STAT3/5/6 transcription factors. Multiple SVs have been reported in both human and mouse resulting in two isoforms of IL-15 molecules being translated (75).…”
Section: Discussionmentioning
confidence: 99%